Molecular screening for proximal 15q abnormalities in a mentally retarded population. Issue 7 (July 1998) - Jacobsen, J; King, B H; Leventhal, B L; Christian, S L; Ledbetter, D H; Cook, E H
Abstract : Paternal or maternal deletions in the 15q11.2-q13 region are known to result in Prader-Willi syndrome (PWS) or Angelman syndrome (AS), respectively. Maternal duplications in 15q11.2-q13 have been found in patients with autism. A population of adults with moderate to profound mental retardation was studied to examine the usefulness of PCR based molecular methods in screening for proximal chromosome 15 abnormalities. Two hundred and eighty-five subjects were initially screened at five microsatellite markers with average heterozygosity values of 0.74 (range 0.54-0.82). Of these subjects, four had a single allele at all five loci, suggestive of a deletion or uniparental isodisomy. The four samples were further screened with additional markers located within 15q11.2-q13 as well as markers telomeric to this region. One subject had uniparental disomy (UPD) and three subjects had a deletion. To determine the parental origin of the 15q11-q13 region containing the single haplotype, samples were analysed with a newly developed methylation specific PCR technique at the SNRPN locus. Each of the four subjects showed presence of the paternal allele and absence of the maternal allele. All cases had a phenotype consistent with Angelman syndrome as expected for the level of mental retardation, but the subject with UPD was distinct from the other subjects with an absence of a history of seizures and presence of bilateral undescended testes and Parkinsonism. Although Angelman syndrome has an estimated population prevalence of 0.008%, at least 1.4% of the moderately to profoundly mentally retarded subjects screened were found to have Angelman syndrome.